CORRELATES OF PHYSICAL ACTIVITY FOR PORTUGUESE ADOLESCENTS ACCORDING TO GENDER (Fiep Bulletin - online, 2014)
Many adolescents have low levels of physical activity (PA).This study sought to identify the factors associated with Portuguese adolescents’ leisure time physical activity (LT PA), according to gender. A total of 336 adolescents (150 boys and 186 girls) aged 17-20 years (17.7±1.0) completed a questionnaire. Questions collected information on LT PA, demographic,  sychological and social variables. Based on LT PA, subjects were assigned as inactive (0-4 times/week) and active (?5 times/week). Logistic regression analyses were applied to the results. The incidence of adolescents in the active groups was low (41% boys, 21% girls). For boys, perceived competence (OR =3.17, p=0.047), mastery orientation (OR =3.08, p=0.036) and perceived health status (OR =2.03, p=0.047) were associated to likelihood to be more active. Conversely, middle education level of parents (i.e., 10-12 years of education) was negatively associated with LT PA (OR =0.19, p=0.023). The model explained 46% of the success to practice LT PA (R2=0.462). For girls, having a high perception of competence (OR =4.56, p=0.003) and height status (OR =1.88, p=0.047) were positive and associated with being more active. The model explained 38% of the LT PA (R2=0.380). The modifiable correlates for adolescents were mainly related to psychological factors. Moreover, correlates  were different for boys and girls, except for the perception of competence. To increase adolescents PA levels it is important to take these differences into account.
Keywords: physical activity; correlates; adolescents; Portugal